Sanctity and legality of transgender: Opinions of eminent scholars and jurisprudence institutions - Dr. Hafiz Hasan Madni; Dr. Saeed Ahmad; Dr. Bashir Ahmad; Dr. Talib Ali Awan (Al-Qanṭara, 2023)
The National Assembly of Pakistan in MayIn 2018, the Transgender Protection Rights Act was passed and implemented across the country. Gender stands for gender and trans stands for: change meaning 'gender transition law'. Sometimes sex change is permissible and sometimes it is a serious sin. Instead of sex change, the most desirable situation should be called 'returning to the original gender reality' and this treatment has also been demanded in Islam. First, the real gender of an individual should be determined. Below is presented the fatwa of Muslim jurisprudence institutions and eminent personalities of the Nation of Islam on this issue.